Cardiac Adaptation of Hungarian Motocross Athletes - Nagy, Arnold; Balogh, László; Vári, Beáta (Arena-Journal of Physical Activities, 2016)
The aim of this study is to examine the Hungarian A- level motocross athletes’ physiological condition during a standardized treadmill stress test. Furthermore, we would like to prove with comparisons to other study results that motocross is a physiologically demanding sport apart from the mental-concentrative and psycho-emotional stress factors. Methods: 6 Hungarian A-level motocross (MX) athletes (age 20.5 s=3,4) took part in our 8 stage treadmill stress test. Before the test we measured EDD, ESD, IVS, PW with an echo and calculated the LVMass(g) = 0,8[1,04[(IVS + PW + EDD)3 -EDD3] - 13,6] + 0,6 and LVMass/ BSA (g/m2). During the test we did EKG. Results(n=6): mean EDD= 53mm (s=2,5); mean ESD= 33mm (s=1,7); mean IVS= 11,8mm (s=1,2); mean PW= 11mm (s=0,6). MX atletes’ mean LVmass is 233,5g (s= 41,2) and the mean LVmass/ BSA is 123,6 g/m2 (s=16,1), while rowers’ LVmass/ BSA= 121,7 g/m2, t(5)= 0,299, p=0,777; and swimmers’ LVMass/ BSA= 125,1 g/m2, t(5)= -0,218, p=0,836 (Vencunas et al.). Resting mean HR was 50,2 min-1 (s=6,7). At the final stage they reached 91% (s=2,2) of their HRmax. HR recovery after 1 min was 78,5% (s=3,8) and after 2 min was 66% of the mean HRmax (r=0,973, p=0,01). Conclusion: The EKG data refers to a well-trained athlete. A-level MX athletes have the same cardiac adaptation to training as a professional or Olympic athlete of the highly dynamic sports.